PENERAPAN CHSE DI RESTORAN BEACH CLUBPADA MASA PANDEMI DI HOTEL PURI SANTRIAN SANUR - I Wayan, Induyoga Aditama; Wiraguna, I Putu Edy; Subadra, I Nengah; Budiasa, I Ketut (HARMONY HOSPITALITY, 2023)
Bali Island is one of the islands in Indonesia which is a destination for both domestic and foreign tourists because the island of Bali has a diversity of cultures and tourism objects. Among the hotels in Bali. Hotel puri santrian sanur is a 5-star hotel located at Jalan.Cemara No.35 Sanur, South Denpasar. To run its daily operations, this hotel has several department restaurants that must provide good service, especially to guests. The first impression of guests towards the hotel is when they see the cleanliness of the restaurant and good service for guests. The purpose of this study was to determine the service procedures at restaurants and the constraints experienced during the current pandemic at Puri Santrian Bali. The type of data used is qualitative data and the data sources used are primary data and secondary data. Data collection techniques used are observation, interview, and documentation techniques. The technique of presenting the results of the analysis used is a comparative descriptive method. The results of the analysis are the implementation of CHSE at the Beach Club Restaurant with the application of strict health protocols in accordance with applicable SOP standards. Constraints faced in determining the CHSE are waiters who do not comply with the CHSE. Steps taken to improve the implementation of CHSE are to provide guidance to all staff regarding CHSE at beach club restaurants.